Wages, housework and attitudes in the Philippines - Dacuycuy, Connie Bayudan- (Animo Repository, 2018)
This paper is one of the few studies that systematically analyzes housework in the Philippines. It seeks to understand how wages and attitudes to work and family life affect the time devoted to housework. Based on different specifications and estimators, our findings indicate that respondents’ own wages are not a significant predictor of the hours they spend on housework but that they are a significant predictor of the time spouses devote to non-market production. We find that husbands’ housework hours are positively affected by female respondents’ wages, while wives’ housework hours are negatively affected by male respondents’ wages. We turn to the Philippine context to explain these results and find the combination of egalitarian society and gender inequality in the labor market to be plausible explanations. Results also show that both wages and attitudes have direct effects on wives’ housework time but that some of the effects of wages are mediated by respondents’ attitudes toward gender roles. JEL code: D13, J22. © 2017, © The Author(s) 2017.